In silico analysis of edible bird’s nest proteins as potential precursors for bioactive peptides - Khuzma Din,; Amiza Mat Amin,; Fisal Ahmad,; Amin Ismail,; Adawiyah Suriza Shuib, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The present study aimed to perform an in silico evaluation of edible bird’s nest protein as potential precursors of bioactive peptides, as well as to determine whether such peptides can be released by selected proteolytic enzymes. Six edible bird’s nest (EBN) protein sequences from a previous study were chosen as potential precursors to produce bioactive peptides via in silico method using the BIOPEP database. AMCase protein sequences gave the highest number of bioactivities (16 to 18) and nucleobindin-2 protein gave the lowest number of bioactivities (9) among the other protein sequences. It was found that the most potential bioactive peptides from EBN proteins are angiotensin-converting enzyme (ACE) inhibitors and dipeptidyl peptidase-IV (DPP-IV) inhibitors. Furthermore, in silico proteolysis using six selected enzymes was employed to release both dominant bioactivities in EBN proteins, which were ACE and DPP-IV inhibitors. This study shows that a combination of enzymes, chymotrypsin, and papain, produced the highest number of activities for both ACE and DPP-IV inhibitor peptides with the frequency of occurrence of bioactive peptides of 0.0968 and 0.1104, respectively. The toxic prediction tool, ToxinPred, found that all EBN peptides derived by in silico analysis were non-toxic. The current study proposed that EBN can serve as a potential source of bioactive peptides.